Low Back Pain Physiotherapy: Does Expectation Really Influence Outcome? - Oen, Alina; Sukmajaya, William Putera; Alkaff, Firas Farisi; Sukmajaya, Alverina Cynthia; Inez, Swan Ien (Open Access Macedonian Journal of Medical Sciences, 2022)
Objectives: Low Back Pain (LBP) is prevalent in most people of working age. The morbidity it causes cannot be taken lightly, as is its economic burden. Physiotherapy has long been prescribed to LBP patients, but treatment outcome measurements, along with the factors influencing it, have not been widely evaluated. In this study, we aim to assess the correlation between patient’s expectation and LBP physical therapy outcome. Methods: This was a cross sectional study conducted at physical rehabilitation outpatient clinic in September-December 2019. Participants were patients with LBP who were treated with physical therapy. One series of physical therapy consists of 5 sessions of modality only or modality with exercise therapy; one patient underwent 2 sessions per week. Oswestry disability index (ODI) score was used to evaluate treatment outcome and Stanford Expectation of Treatment Scale score was used to evaluate patient’s expectation. Data was collected twice, before and after 1 series of therapy. Results: There were 91 participants included in this study, most of whom were female. Most patients reported a significant decrease in ODI score, irrespective of the LBP chronicity or nutritional status. However, patients who received a combination of physical exercises and modalities reported lower after therapy ODI than those who only received modalities (p=0.009). No correlation was found between positive (p=0.567) or negative (p=0.910) expectations with ODI improvement. Conclusion: Our study did not find any correlation between positive or negative expectations towards ODI score improvement. Keywords: Low back pain; Physical therapy; Treatment outcome; Patient expectation; ODI score